2013
DOI: 10.1210/en.2012-1994
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Stimulates Ghrelin Secretion Through the Activation of MAPK and EPAC and Potentiates the Effect of Norepinephrine

Abstract: Ghrelin is a stomach-derived orexigenic hormone whose levels in circulation are altered by energy availability. Like ghrelin, the glucotropic hormone glucagon increases in the fasting state and serves to normalize energy levels. We hypothesized that glucagon can directly stimulate stomach ghrelin production. To verify this hypothesis, we used a primary culture of dispersed rat stomach cells. We first demonstrated that stomach ghrelin cells express the glucagon receptor (GluR). Glucagon (1-100 nM) significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…57 Thus, ghrelin directly stimulates glucagon secretion from pancreatic α cells (via GHS-R), 90 while glucagon stimulates ghrelin secretion under nutrient-deficient conditions. 91 Studies on laboratory animals have revealed that under the action of acyl-ghrelin, fat is stored not only in adipose tissue but also the liver, 39 where an increase in triacylglycerol content and genes involved in hepatic lipogenesis was found. 92 A recent study published by Gagnon et al brought up for discussion a new aspect of ghrelin involvement in glucose regulation, the authors demonstrating that ghrelin increases the secretion of GLP-1 (glucagon like peptide 1), thereby improving glucose tolerance.…”
Section: Ghrelin and Intermediary Metabolismsmentioning
confidence: 99%
“…57 Thus, ghrelin directly stimulates glucagon secretion from pancreatic α cells (via GHS-R), 90 while glucagon stimulates ghrelin secretion under nutrient-deficient conditions. 91 Studies on laboratory animals have revealed that under the action of acyl-ghrelin, fat is stored not only in adipose tissue but also the liver, 39 where an increase in triacylglycerol content and genes involved in hepatic lipogenesis was found. 92 A recent study published by Gagnon et al brought up for discussion a new aspect of ghrelin involvement in glucose regulation, the authors demonstrating that ghrelin increases the secretion of GLP-1 (glucagon like peptide 1), thereby improving glucose tolerance.…”
Section: Ghrelin and Intermediary Metabolismsmentioning
confidence: 99%
“…Although some studies 88 found no correlation between ghrelin and leptin levels in obese children and adolescents, other studies suggest that there is a complex interaction between leptin and ghrelin. 89 Immunoneutralisation of circulating plasma ghrelin with specific immunoglobulin (Ig)-G anti-ghrelin antibodies caused a marked increase in plasma leptin and decrease in food intake.…”
Section: Leptin (Ghrelin-leptin Tango)mentioning
confidence: 94%
“…Most human studies [184][185][186][187] except for one [119] have reported that glucagon suppresses circulating ghrelin levels, whereas in rats glucagon stimulates ghrelin secretion [63, 188,189].…”
Section: Glucagonmentioning
confidence: 99%
“…Systemic administration of isoproterenol increases plasma ghrelin levels, whereas atenolol and reserpine suppress fasting-induced elevation of ghrelin [30,225]. Ghrelin-producing cells express the α1 and β1 adrenergic receptors [30,32,55], and adrenaline and noradrenaline directly stimulate ghrelin secretion via the β1 receptor [30,55,62,171,188]. Activation of the β1 receptor results in elevation of intracellular cAMP, followed by Ca 2+ release from ER and granular exocytosis.…”
Section: Neural Control Of Ghrelin Secretionmentioning
confidence: 99%